The role of the cost system based on activities as an effective method of cost management in achieving the lower cost advantage of Algerian economic institutions Case Study of a Sample of Algerian Economic Institutions in Annaba - messaoudi, sara; semmeche, kamel (Journal of Research in Finance and Accounting, 2026)
The study aimed to demonstrate the importance of applying the cost system on the basis of activities as an effective method of cost management and its role in enhancing competitiveness by achieving the lower cost advantage of Algerian economic institutions, highlighting the most important obstacles to its application, and to that end the study used a questionnaire to monitor the views of marchers in Algerian economic institutions in Annaba state, and to analyse these views using statistical programmes to reach sound results as a basis on which the results of the study are based. The study found that the activities-based cost system provides accurate information to facilitators about costs, enabling them to make sound and rational decisions in a timely manner, allowing for cost-effectiveness and enhanced prestige and competitiveness, but that the actual application of the system at the enterprise level is almost non-existent due to the many difficulties that prevent its application.